HUBUNGAN BIG FIVE PERSONALITY DENGAN KOMITMEN ORGANISASI PADA PEGAWAI BADAN NARKOTIKA NASIONAL KOTA MANADO - Lita Abung, Geovani; Lenny Mangantes, Meisie; B. Sengkey, Stevi (Penerbit Lafadz Jaya, 2026)
This study investigates the relationship between Big Five Personality traits and organizational commitment among employees of the National Narcotics Agency (BNN) in Manado City, where high-risk work demands strong psychological attachment. The objective was to examine this correlation quantitatively. A correlational design with total sampling involved 67 BNN employees. Instruments included Big Five Personality Scale and Organizational Commitment Scale (Likert format), analyzed via Pearson Product Moment correlation using SPSS 25, following normality (sig=0.200) and linearity (sig=0.452) tests. Results revealed a significant positive relationship (r=0.627; p<0.05), with Conscientiousness, Openness, Agreeableness, and Extraversion positively correlated, while Neuroticism showed negative correlation (R²=0.393). In conclusion, personality traits substantially influence commitment, informing recruitment and stress management strategies.